Patient experiences with designated service provider medication delivery in a rural general practice in KwaZulu-Natal: a cross-sectional study on HIV patients - V. V. Reddy; O. H. Mahomed (South African Family Practice)
Background: Healthcare funders (medical schemes) have established disease management programmes (DMPs) and designated service providers (DSPs) to reduce costs and improve patient outcomes to meet legislative requirements. However, there is a paucity of studies that have researched patient experiences and adherence to medication through the DSP process.